Understanding the role of green infrastructure in climate change resiliency of transportation infrastructure - Thomas, Victoria Saunders (Kansas State University, 2020)
The Earth’s climate is currently changing faster than at any point in the history of modern civilization, primarily as a result of human activities (Reidmiller et al., 2018). In addition to increases in very hot days and heat waves, more frequent and intense extreme weather events are expected (Herring et al., 2019; Reidmiller et al., 2018; Transportation Research Board, 2008) Trenberth, 2011). The increased flooding caused by the intensification of the hydrologic cycle heightens the risk to America’s aging transportation infrastructure. The intent of this research is to understand if and to what extent green infrastructure can increase the climate change resiliency of transportation infrastructure across a watershed. To meet this objective, a Personal Computer Storm Water Management Model (PCSWMM) of the Blue River Watershed (BRW) in the greater Kansas City Metropolitan Area created by Kelsey McDonough (2018) was adapted and updated. Twelve different low impact development scenarios with varying levels of green infrastructure were evaluated across a range of design storm events in both one and two-dimensional models. The percent reduction in peak flow, total volume of flow, and flood extent between each scenario and the current conditions were evaluated. Results demonstrate that increasing the percentage of “disconnectedness” i.e. water flows from impervious surfaces onto vegetated surfaces before reaching streams, and adding a 150 foot riparian buffer significantly decreased the simulated peak inflow and total volume of water near important transportation infrastructure. The reductions were greatest for the water quality event (>90% reduction) and decreased to an approximately 10% reduction for the 100 year, 24 hour storm event for the maximum green infrastructure scenario. Increasing disconnectedness to at least 25% with the riparian buffer reduced flood extent approximately 8% for the 1, 5, and 10-year design storms. Minimal flood extent reductions were seen for the 100-year design storm. These results indicate that increasing green infrastructure does increase the climate change resiliency of transportation infrastructure, however additional structural flood control is needed to reduce flood extent greater than 10% and for flood control of design storms of 100+ years.
Keywords: Green infrastructure; Climate change resiliency; Hydrologic modeling; Transportation Resiliency; Low Impact Development; Flooding